Evaluation Analysis of Scheduling and Monitoring of the Construction Project for the Rehabilitation of SDN 18 Kampung Baru 1, Monterado, Bengkayang, West Kalimantan - Surugallang, Mutiara Pasande; sari, sely novita; maulana, rizal (ReTII, 2021)
Project evaluation and monitoring is an important part of project management. It is very necessary to know what work has been done on the project and how to deal with any delays in work or deviations from costs. This study aims to determine the results of the evaluation of project scheduling and monitoring as well as the benefits of project monitoring Project scheduling evaluation analysis is carried out by comparing the planned s-curve with the realization s-curve, by calculating the deviation value for the project. While monitoring is done using the earned value concept with initial data analysis of earned value indicators, analysis of changes and analysis of estimates. The results of the evaluation of scheduling and research monitoring show that in scheduling the deviation value every week there are still many negative values, this is because the project under study has only been carried out after the first phase of disbursement of funds. The results of monitoring using the earned value concept produce work performance values, and estimated time for completion of work, but monitoring of costs cannot be carried out because the actual cost